LIBERO`S FUNCTION ON THE SERVICE RECEPTION AND DEFENSE DURING THE MATCHES OF THE FEMALE VOLLEYBALL SUPERLEAGUE 2009/2010. (Fiep Bulletin - online, 2011)
The objective of this scientific investigation was to identify the effectiveness, the efficiency and the error of the libero player on the service reception and defense. 11 matches were filmed and then analyzed, accounting 44 sets, belonging to 8 teams that were participating of the 2009/2010 volleyball superleague in games that occured in Recife-PE. 758 actions of service reception were analyzed, where 203 were performed by the libero and 555 by the other players, and 1008 defense actions, where 278 were performed by the libero and 730 by the other players. As performance indicatives, we used the effectiveness, the efficiency and the error of the actions of service reception and defense executed by the libero, which were distributed in scales that ranged from 0 to 3 scores. The descriptive statistics used were the mean, standart deviation and frequency percentual distribution. To evaluate the differences among the variables we used Student`s t test with a significance level of p
Keywords: Volleyball; Libero player; Reception; Defense